Evaluation of teaching effect of first-aid comprehensive simulation-based education in clinical medical students - Peng, Mian; Su, Ning; Hou, Rui; Geng, Huijuan; Cai, Fangfang; Zhong, Weixiong; Zhang, Weifang; Zhong, Jingxing; Yang, Zhengyue; Cao, Weiling (Frontiers in Public Health, 2022)
Although students mastered the composition skills, they lack of the ability to effectively integrate these composition skills in real clinical situations. To address the problem, we set up different levels of situational simulation training for grade 2 ~ 4 medical students, and evaluate the teaching effect of first aid situation comprehensive simulation-based education on clinical medical students.